A new method for preparation of PS‐g‐PA6 grafted copolymer micelles. (28th September 2017) - Liu, Yan; Jiang, Qiyong; Wang, Xiaojun; Li, Jing; Chu, Xiaohui; Wang, Jinjun; Jin, Haizhu
Abstract : This work described a new method for the synthesis of PS‐g‐PA6 grafted copolymer micelles. PS‐g‐PA6 sphere micelles were synthesized by using a same solvent at the absence of selective solvent. The morphologies of micelles were characterized by SEM and TEM. The PS‐g‐PA6 micelles loaded Fe3 O4 particles have better MRI imaging effect. The synthesis strategy developed here may present a desirable way to fabricate grafted copolymer micelles.